2016
DOI: 10.1007/s12039-016-1194-x
|View full text |Cite
|
Sign up to set email alerts
|

Is dynamic heterogeneity of water in presence of a protein denaturing agent different from that in presence of a protein stabilizer? A molecular dynamics simulation study

Abstract: Rotational and translational dynamic heterogeneities (DHs) of ambient aqueous solutions of trimethylamine-N-oxide (TMAO) and tetramethylurea (TMU) at several solute concentrations have been investigated and compared. Motional characteristics of water molecules at solute interfaces and in bulk solutions have been thoroughly examined for the search of slow dynamics. Note, TMAO possesses zwitterionic structure and is a protein stabilizer whereas TMU is a neutral dipolar molecule and a strong denaturant. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 69 publications
4
14
0
Order By: Relevance
“…The sluggish translational, rotational and hydrogen bond dynamics for the three components in PWUC system confirm the correlated slowdown of all the three components around the protein, which can also be attributed to the spatial arrangement of the bulky molecules of denaturant and the protecting osmolyte. This kind of slower motion of water and other co‐solvents around a protein is also reported earlier for different denaturants or protecting osmolytes . This type of dynamics modulates the rigidity of the surrounding environment and turns it into a slowly moving solvent shell around the protein which imposed a restriction in conformational flexibility of protein in the ternary mixture and even in PWC system reflected in the RMSD‐vs‐R g plot (Figure ).…”
Section: Discussionsupporting
confidence: 76%
“…The sluggish translational, rotational and hydrogen bond dynamics for the three components in PWUC system confirm the correlated slowdown of all the three components around the protein, which can also be attributed to the spatial arrangement of the bulky molecules of denaturant and the protecting osmolyte. This kind of slower motion of water and other co‐solvents around a protein is also reported earlier for different denaturants or protecting osmolytes . This type of dynamics modulates the rigidity of the surrounding environment and turns it into a slowly moving solvent shell around the protein which imposed a restriction in conformational flexibility of protein in the ternary mixture and even in PWC system reflected in the RMSD‐vs‐R g plot (Figure ).…”
Section: Discussionsupporting
confidence: 76%
“…[58][59][60][61][62][63] Molecular dynamics simulations have shown that water-TMAO interaction is stronger than that of watertetramethylurea. 64 This is in line with an earlier study by Paul et al 65 Despite having a similar structural framework, tert-butyl alcohol and TMAO show a drastic difference in their behaviors on the water structure. 26 The presence of multiple potential hydrogen bonding sites is responsible for the interference of urea into the tetrahedral structure of water.…”
Section: Introductionsupporting
confidence: 88%
“…τ In our case, the simulated value of the ratio of translational and rotational diffusion constant (D T /D R ) is not equal to the value obtained from the hydrodynamic prediction. A recent simulation study 38 has also shown the similar kind of break-down of this expected constancy even for ambient aqueous solutions.…”
Section: Coupling Between Translational and Rotational Diffusionsupporting
confidence: 56%